(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The purpose of this paper was to determine if a difference in achievement scores exist between students who attended the School System preschool program and those who did not as measured by standardized achievement test Reading/Language Arts and Math scores of students in the third and fourth grades. The variables of grade level and preschool attendance were considered. The population consisted of students who were in the third or fourth grades in the School System during the 2010-2011 school years through the 2012-2013 school years. Data gathered were from the Tennessee Comprehensive Assessment Program achievement test scores obtained from the 2010-2011 school year through 2012-2013 school years and from the preschool attendance student management system. Independent and paired t-tests were used to evaluate differences in the variables. The investigation of the relationship between attendance in preschool and achievement test scores might assist educators in planning and implementation of future preschool programs within the public school setting. Findings in this study did not show significance of preschool attendance within the School System preschool program in relation to achievement test scores. Scale scores were tested in this model for both third and fourth grade achievement scores. These scores consisted of Reading/Language Arts and Math. Areas tested were found to have no significant differences for third and fourth grade based on preschool attendance but did have significant differences when third grade was compared to fourth grade of the same students.